Reduced CCR6+IL-17A+Treg Cells in Blood and CCR6-Dependent Accumulation of IL-17A+Treg Cells in Lungs of Patients With Allergic Asthma - Shen, Xiaokun; Zhang, Huiyun; Xie, Hua; Chen, Liping; Li, Shinan; Zheng, Junjuan; Chai, Ruonan; Wang, Zhao; Zang, Yanyan; He, Shaoheng (Frontiers in Immunology, 2021)
Human regulatory T (Treg) cells play a central role in controlling allergic inflammation in the airways. A reduced number of peripheral Treg cells and decreased suppressive function have been previously reported in the pathogenesis of allergic asthma. However, the characteristic role of specific Treg cell subsets and their mechanisms in the pathogenesis of allergic asthma remain unclear. In this study, we examined the proportion of different Treg cell subsets in both healthy subjects and patients with allergic asthma using flow cytometry and single-cell RNA sequencing. The migration function of the cells was compared using cell sorting and Transwell experiments. Furthermore, two allergen-challenged mouse models and a cell transfer experiment were used to examine the role of these Treg subsets. We found that the proportion of CD25+Foxp3+CD127- Treg cells in the peripheral blood of patients with allergic asthma was lower than in those of healthy subjects. Furthermore, the circulating Treg cells expressed lower levels of CCR6 and IL-17 compared with healthy subjects. The chemokine from the airway mucosa, CCL20, was abundantly expressed, and Transwell experiments further proved that this chemokine promoted CCR6+ Treg cell migration in vitro. A mouse model induced by house dust mite (HDM) revealed that the number of CCR6+ Treg cells in the lung tissue increased remarkably. The incidence of allergic asthma may be related to an increase in Treg cells secreting IL-17 in the lung tissue. Recruited CCR6+ Treg cells are likely to differentiate into Th17-like cells under the Th17 environment present in the lungs. IL-17 derived from Th17-like cells could be associated with the pathology of allergic asthma by promoting Th17 responses, thereby favoring HDM-induced asthma exacerbations.